2016
DOI: 10.3325/cmj.2016.57.591
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of out-of-hospital cardiac arrest in Croatia – survival, bystander cardiopulmonary resuscitation, and impact of physician’s experience on cardiac arrest management: a single center observational study

Abstract: AimTo analyze the initial rhythm, bystander cardiopulmonary resuscitation (CPR) rate, and survival after out-of-hospital cardiac arrests (OHCA) in Varaždin County (Croatia), and to investigate whether physician’s inexperience in emergency medical services (EMS) has an impact on resuscitation management.MethodsWe reviewed clinical records and Revised Utstein cardiac arrest forms of all out-of-hospital resuscitations performed by EMS Varaždin (EMSVz), Croatia, from 2007-2013. To analyze the impact of physician’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 31 publications
0
14
0
2
Order By: Relevance
“…The CPR literature lacks consensus among the authors on the impact of witnessed CPR on the outcomes of OHCA. Shimamoto et al [27] indicated that in nursing homes, bystander CPR was not associated with improved outcomes of OHCA. This is also confirmed by Lukić et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…The CPR literature lacks consensus among the authors on the impact of witnessed CPR on the outcomes of OHCA. Shimamoto et al [27] indicated that in nursing homes, bystander CPR was not associated with improved outcomes of OHCA. This is also confirmed by Lukić et al [28].…”
Section: Discussionmentioning
confidence: 99%
“…Istraživan-ja iz zemalja regiona ukazuju da je približno slična situacija. U Hrvatskoj [4] je procenat započinjan-ja mera osnovne životne podrške od strane svedoka 25%, u Sloveniji 23%. Prema podacima ovog istraživan-ja, procenat osvedočenih srčanih zastoja zavisi od mesta događaja.…”
Section: Diskusijaunclassified
“…Two smaller non-RCTs examined subgroups of OHCAs and also found no association between survival to discharge and the experience of the individual treating paramedics or treating EMS team. 193,197 The remaining non-RCT reported an association between increased survival to hospital discharge and technicians with more than 4 years of experience (adjusted OR 2.58; 95% CI, 1.11À6.03; P = 0.03) and paramedics with more than 1 year of experience (adjusted OR 2.68; 95% CI, 1.05À6.82; P = 0.04). 194 However, this study did not fully account for the experience of the paramedics because it did not include the previous career experience of paramedics as EMTs.…”
Section: Consensus On Sciencementioning
confidence: 99%